2008
DOI: 10.1002/jsfa.3235
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid and fat‐soluble antioxidant concentrations in milk from high‐ and low‐input conventional and organic systems: seasonal variation

Abstract: BACKGROUND: Previous studies showed differences in fatty acid (FA) and antioxidant profiles between organic and conventional milk. However, they did not (a) investigate seasonal differences, (b) include non-organic, lowinput systems or (c) compare individual carotenoids, stereoisomers of α-tocopherol or isomers of conjugated linoleic acid. This survey-based study compares milk from three production systems: (i) high-input, conventional (10 farms); (ii) low-input, organic (10 farms); and (iii) low-input non-org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

46
239
11
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 220 publications
(324 citation statements)
references
References 41 publications
46
239
11
9
Order By: Relevance
“…However, there are some studies present contradictory results. Butler et al (2008) found a higher protein content in organic than in conventional milk but Toledo-Alonzo (2003), Zagorska and Ciprovica (2008), and Stergiadis et al (2012) showed no difference in protein and/or casein contents between organic and conventional milks. The lower content of protein in organic milk can be explained by the lower amount of starch in organic diets which results from the lower amounts of concentrate feeds provided to cows.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…However, there are some studies present contradictory results. Butler et al (2008) found a higher protein content in organic than in conventional milk but Toledo-Alonzo (2003), Zagorska and Ciprovica (2008), and Stergiadis et al (2012) showed no difference in protein and/or casein contents between organic and conventional milks. The lower content of protein in organic milk can be explained by the lower amount of starch in organic diets which results from the lower amounts of concentrate feeds provided to cows.…”
Section: Resultsmentioning
confidence: 94%
“…There are a number of comparative studies on the composition and properties of organic and conventional cows' milks. According to some authors, milk from organically certified systems contains more polyunsaturated fatty acids including n-3 polyunsaturated fatty acids and CLA (Ellis et al 2006;Bloksma et al 2008;Popović-Vranjes et al 2010;Butler et al 2011b), vitamins, and calcium (Bergamo et al 2003;Butler et al 2008). The more favourable fatty acids profile of organic milk in these studies has been mainly associated with organic diets richer in fresh grass and clover which conventional diets are based on silage and concentrates.…”
mentioning
confidence: 98%
“…The concentrations of α-tocopherol and β-carotene are higher in organic than conventional milk during the outdoor feeding period, but not during the indoor feeding period in the study of Butler et al (2008). Ellis et al (2007) reported no differences for these vitamins, but found less retinol in organic milk.…”
Section: Introductionmentioning
confidence: 82%
“…Compared with conventionally produced milk, organically produced milk has higher fat proportions of C18:3n-3 (Butler et al, 2008;Collomb et al, 2008a), C18:1 trans-11 and C18:2 cis-9,trans-11 (Jahreis et al, 1996;Collomb et al, 2008a), PUFA (Ellis et al, 2006;Collomb et al, 2008a), and lower proportions of n-6 FA (Butler et al, 2008;Collomb et al, 2008a;), C18:0, C18:1 cis-9, and MUFA (Jahreis et al, 1996;Collomb et al, 2008a). The concentrations of α-tocopherol and β-carotene are higher in organic than conventional milk during the outdoor feeding period, but not during the indoor feeding period in the study of Butler et al (2008).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, simple liquid meals (for example, cream added to a liquid meal replacement) allow for better control of the nutrient composition from subject to subject. If foods are included that naturally vary in composition throughout the year (for example, dairy products 30 ), it is advantageous to take an aliquot of the homogenized meal for analysis of its macronutrient content and fatty acid composition. Further, the use of commercially available liquid formulas allows variability in the quantity fed to different subjects based on their daily energy needs, maintenance of constant food composition and standardization of the meal composition across multiple research sites.…”
Section: Meal Detailsmentioning
confidence: 99%